Genomic characterization of Leishmania (V.) braziliensis associated with antimony therapeutic failure and variable in vitro tolerance to amphotericin B - Laura Natalia Gonzalez-Garcia; Aura María Rodríguez-Guzmán; Carolina M. Vargas-León; Samanda Aponte; Liliana A. Bonilla-Valbuena; J. Manuel Matiz-González; Ana M Clavijo-Vanegas; Germán Andrés Duarte-Olaya; Catherine Aguilar-Buitrago; Daniel Alfonso Urrea; Jorge Duitama; Maria C. Echeverry (Scientific Reports)
Abstract Leishmaniasis, a vector-borne disease caused by protozoa from the Leishmania genus, presents a wide range of clinical manifestations in humans and varying responses to treatments. The main clinical presentations correspond with visceral leishmaniasis (VL), cutaneous leishmaniasis (CL), and mucosal leishmaniasis (ML). Amphotericin B (AmB) is a second-line therapeutic option in all forms of leishmaniasis with treatment failure or contraindication for Antimony derivates (SbV) therapy and in geographical regions with a high prevalence of SbV-resistant parasites. This study delves into the genomic features of thirteen L. (V.) braziliensis clinical isolates from CL patients who experienced therapeutic failure to SbV treatment. The isolates were categorized based on their AmB in vitro susceptibility in the amastigote stage, the intracellular parasitic form found in the vertebrate host. The whole genome sequences of the isolates were analyzed and compared with the reference genomes of L. (V.) braziliensis (MHOM/BR/75/M2904 and M2903). The average number of heterozygous SNPs in clinical isolates is at least 75% higher than the reference genomes, and the allele dosages suggest an overall ploidy of two, except in chromosome 31. The main mutations associated with AmB resistance previously reported in experimental cell lines from L. (L.) infantum, L. (L.) mexicana, and L. (L.) donovani were not found in this study. However, there were found mutations referred by other authors in parasites resistant to antileishmanial drugs in proteins such as GP63 (leishmanolysin), NADH-ubiquinone oxidoreductase- ESSS subunit- (putative), quinonoid dihydropteridine reductase, 20s proteasome beta 7 subunit- (putative), biopterin transporter- (putative), and common hypothetical proteins. CNV analysis revealed that the isolates most tolerant to AmB present duplications of genomic regions encompassing genes involved in N-Glycan biosynthesis and biopterin/folate transport and metabolism. Therefore, the present study uncovers previously undescribed metabolic pathways that could be involved in the natural AmB tolerance in Leishmania, which need to be functionally evaluated. These findings highlight the need for further drug response studies in field isolates.